2005
DOI: 10.1111/j.1600-0447.2004.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Aversive tension in patients with borderline personality disorder: a computer‐based controlled field study

Abstract: The study provides support for the theory that patients with BPD experience more frequent, stronger, and longer-lasting states of aversive tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
170
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(192 citation statements)
references
References 22 publications
16
170
0
6
Order By: Relevance
“…The latter regions have been addressed by numerous neuroimaging studies in patients with BPD, 2,3 although mostly within the context of cognitive, affective and somatosensory stimulation. Since a range of clinical features of BPD might especially occur in reaction to (mostly negative) experiences, 56 networks subserving cognitive control functions as a response to environmental demands might appear intact when studied under resting-state conditions. Thus, further research is needed to dissociate alterations of brain network connectivity during experimentally induced conditions and their interactions with baseline connectivity during the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…The latter regions have been addressed by numerous neuroimaging studies in patients with BPD, 2,3 although mostly within the context of cognitive, affective and somatosensory stimulation. Since a range of clinical features of BPD might especially occur in reaction to (mostly negative) experiences, 56 networks subserving cognitive control functions as a response to environmental demands might appear intact when studied under resting-state conditions. Thus, further research is needed to dissociate alterations of brain network connectivity during experimentally induced conditions and their interactions with baseline connectivity during the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…Domes et al [26] found that the recognition performance of BPD patients increased over the course of the experiment when compared to the controls, whereas Merkl et al [31] did not. Other studies found BPD patients to have difficulties in differentiating the perception of their own emotional states [9,32,33]. In sum, the studies on facial emotion recognition so far suggest that BPD is associated with subtle differences in facial emotion recognition, maybe best described as being biased towards a high sensitivity for social signals of threat and rejection, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…56 Acute dysfunctional behaviors characteristic of BPD often occur in reaction to stressful situations. 57 A specific vulnerability to stress (higher emotional intensity in response to stressors and a delayed return to baseline affect) has been proposed for individuals with BPD, 58 which might be associated with the hypothalamic-pituitary-adrenal axis (HPAA). 59 Adults with BPD show an attenuated cortisol response to acute stress, 60 and this has also been found in adolescents engaging in repetitive NSSI.…”
Section: Neurobiological Findingsmentioning
confidence: 99%